In Vitro Interactions of Ciprofloxacin with Selected Drugs and Excipients - Poudel, B.K.; Thapa, Panna (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The present work comprises an interaction studies of ciprofloxacin, a quinolone antibiotic, with drugs (raw and market products) and excipients (raw and market products). For this, all the reaction conditions were simulated to gastric and intestinal environment. Drug-ciprofloxacin interactions were studied in USP Type II dissolution apparatus for three hours, aliquots of medium sampled out at an interval of 30 minutes. For excipients, fixed concentration of ciprofloxacin was mixed with varied ratio of excipients, shaken in an orbital shaker up to equilibrium time. The contents of ciprofloxacin in both processes were determined in UV spectrophotometer. The results revealed that both raw and market drugs: calcium hydroxide, aluminium hydroxide, magnesium hydroxide, sodium bicarbonate, calcium carbonate, marketed calcium carbonate tablets and marketed magnesium trisilicate suspension retarded the in vitro availability of ciprofloxacin in both simulated gastric and intestinal fluids. Further, binding of ciprofloxacin to talc, starch and microcrystalline cellulose was found to be non-linear but linear with activated charcoal and bentonite. While studying on two different formulations of activated charcoal, it was found that the maximum adsorption capacity for D-Tox capsules was 254.48 (simulated gastric fluid) to 232.63 (simulated intestinal fluid) and for D-Tox powder was 379.86(simulated gastric fluid) to 353.61 (simulated intestinal fluid) respectively. The effect of pH on binding to activated charcoal was not statistically significant. The binding of ciprofloxacin to drugs was found to be statistically significant and presumed to be due to chelation. The values of T50% and T90% increased drastically in both simulations, effect more pronounced in simulated intestinal fluid. Therefore, availability of ciprofloxacin can be affected by concurrent ingestion of aforementioned drugs or excipients.